Efficient Utilization of Almond Shell Biochar and Silica Fume for Normal Strength Concrete to Develop Eco-Friendly Concrete - Tanrikulu, Merve Esen; Demir, Tuba (Mdpi, 2025)
The aim of this study is to investigate the potential use of rapidly increasing agricultural wastes in concrete production by substituting them for cement, thereby reducing their environmental impact and producing eco-friendly concrete. For this purpose, concrete samples were produced using a combination of almond shell biomass (ASB) and silica fume (SF). These samples were subjected to standard compressive strength tests as well as ultrasonic pulse velocity (UPV), porosity (P), and maturity (M) tests. In addition, the microstructure of the samples containing ASB and SF was examined using scanning electron microscopy (SEM). The test results show that the combined use of ASB and SF in concrete production significantly improves the strength properties, and the best results were obtained from the ASB6SF10 series. A significant increase of 37.7% was observed in the compressive strength values of the ASB6SF10 series from the early age between 3 and 28 days. UPV and P values were obtained as 4.46 m/s and 10%, respectively. The use of ASB and SF in concrete production has been found to be critically important in terms of the mechanical and physical properties of concrete and environmental benefits. The results of the study show that ASB and SF have potential for use in concrete production and can contribute to more sustainable concrete production, waste management, and the circular economy by reducing the negative environmental impacts arising from this production.
Keywords: agricultural waste; eco-friendly concrete; almond shell biochar; SEM; waste management